PERFORMANCE EVALUATION OF NATURAL CONVECTION INDIRECT SOLAR DRYER FOR DRYING WHITE YAM SLICES - Braihma, Y.; Yola, I. A. (FUDMA JOURNAL OF SCIENCES, 2023)
This paper presents the performance evaluation of a natural convection indirect solar dryer for drying white yam. Drying is the process of removing enough moisture from food to prevent decay and spoilage. Large quantity of yams are produced, therefore, there is need for drying the yams to minimize wastage. This study mainly tried to solve the problem of post harvest-loss using natural convection indirect solar dryer for drying white yam. The dryer was made from plywood with 10 mm thickness and consists of a solar collector and drying chamber which houses three trays with an upper vent for the exit of air. The result of no load showed that the dryer temperature could rise up to 60 . The average collector temperatures recorded from no load tests were 71.1 oC and 75.11 oC. The collector efficiency was found to be 53.1 and dryer efficiency was 10.5 . The drying rates for the load tests were found to be 0.081 kg/hr and 0.095 kg/hr. It was found that, the required 7.6% moisture content was obtained within 18 hours of drying. Therefore, farm products with an initial moisture content of 71.3% can be dried using this dryer.